Stable and Dendrite‐Free Lithium Metal Anodes Enabled by Ionic/Electronic Li2S/Mo Interlayer - Lishuang Fan (Wiley-VCH, 2021)
The wide applications of high‐capacity lithium metal anodes for lithium metal batteries are restricted by the uncontrollable lithium dendrite growth caused by the uneven lithium deposition and the infinite volume change of lithium anodes during the plating/stripping process. Herein, the composite ionic/electronic interlayer of Li2S/Mo is deposited on the surface of stainless steel mesh (SSM) by in situ electrochemical conversion reaction from MoS2 nanosheet arrays. The Li2S/Mo interlayer with high ionic conductivity can regulate uniform lithium‐ion flux and promote homogeneous lithium deposition without dendrite growth. The half cells with Li2S/Mo‐modified SSM current collector show stable cycling performance of more than 400 cycles at 1 and 1 mAh cm−2, with the average Coulombic efficiency higher than 96%. By coupling with LiFePO4 cathodes, the assembled full cells demonstrate improved cycling performance. This work provides a new idea for using metal sulfides as a lithiophilic interlayer to facilitate dendrite‐free lithium deposition.